A PCR-based protocol to accurately size C9orf72 intermediate-length alleles. (April 2017) - Biasiotto, Giorgio; Archetti, Silvana; Di Lorenzo, Diego; Merola, Francesca; Paiardi, Giulia; Borroni, Barbara; Alberici, Antonella; Padovani, Alessandro; Filosto, Massimiliano; Bonvicini, Cristian; Caimi, Luigi; Zanella, Isabella
Abstract: Although large expansions of the non-coding GGGGCC repeat in C9orf72 gene are clearly defined as pathogenic for Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Lobar Degeneration (FTLD), intermediate-length expansions have also been associated with those and other neurodegenerative diseases. Intermediate-length allele sizing is complicated by intrinsic properties of current PCR-based methodologies, in that somatic mosaicism could be suspected. We designed a protocol that allows the exact sizing of intermediate-length alleles, as well as the identification of large expansions. Highlights: Large GGGGCC expansions in C9orf72 gene are frequent genetic cause of ALS and FTLD. Intermediate GGGGCC expansions in C9orf72 gene are also associated with ALS and FTLD. Intermediate-length alleles are also associated with other neurodegenerative diseases. Current PCR-based methods may lead to incorrect sizing of intermediate-length alleles. Our PCR-based protocol exactly sizes C9orf72 intermediate-length alleles.